If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -37(14x) + 28(21x) = 72 + -72 + -166 + 96 Remove parenthesis around (14x) -37 * 14x + 28(21x) = 72 + -72 + -166 + 96 Multiply -37 * 14 -518x + 28(21x) = 72 + -72 + -166 + 96 Remove parenthesis around (21x) -518x + 28 * 21x = 72 + -72 + -166 + 96 Multiply 28 * 21 -518x + 588x = 72 + -72 + -166 + 96 Combine like terms: -518x + 588x = 70x 70x = 72 + -72 + -166 + 96 Combine like terms: 72 + -72 = 0 70x = 0 + -166 + 96 70x = -166 + 96 Combine like terms: -166 + 96 = -70 70x = -70 Solving 70x = -70 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '70'. x = -1 Simplifying x = -1
| (7+2i)/(3-3i) | | 4(x-4)+2x-3=4(4-x) | | 3n^2=-10n-4 | | 16y-5+2y=70 | | ((6x+18)/(5x^2))/((6x^3)/(25)) | | X^2-60x+960=0 | | x^2+15x=450 | | x^2+11x=350 | | 6x^3-29x^2+4x-45=0 | | 6(1-x)-2(x-2)=2-4(x-4) | | x^2+11=350 | | (1/5)(45-X) | | (2x+5)/(7x+22) | | 12x+15y=1000 | | 9-21=y-2+16 | | 75=n+4n | | 87-116=-4(-4y)-9(2y)+y | | N^3=-35-12n | | X^2+6x-r=-9 | | 24=2g-6 | | -1/7+7=5/7 | | (3x^2+2x-1)-(x^2-4x-7)= | | (3x^2+7x+9)-(7x-8)= | | (-4x^2+10x+15)+(3x^2-2x-4)= | | (3x^2-x+2)(16-x^2)= | | 2y-(3+7y)=11-3y | | (7x^2-14x+25)+(3x^2+3x-4)= | | -90=-10(-3b) | | x^3=5x-4x^2 | | (3x^2-4x+2)+(x^2+3x-4)= | | 4e+9= | | -(2-4(-3+1)+2)/9(-1-2) |